Formation of Army of the Republic of Kazakhstan in post-Soviet period - Bogdan Levyk (Cхід, 2013)
The process of forming the armed forces of theRepublicofKazakhstanin post-Soviet period has been analyzed. The most important legislative acts defining military and political issues in national legislation have been considered. The armed forces organizational structure as well as its technical equipment have been covered extensively.